Independence with interdependence : inventing a Parliament for the Caribbean region. - SANDIFORD, Lloyd Erskine (1997)
Calls for a new kind of political and organizational entity based on recognition of both territorial independence and regional interdependence in matters of mutual interest. Points out that the Assembly of Caribbean Community Parliamentarians can help in this process.